Konflik Yang Represif: Studi Kasus Terhadap Pasujudan Santri Luwung Padepokan Bumi Arum Di Sragen - Arnis Rachmadhani (LP2M UIN Sunan Kalijaga, 2017)
This qualitative reserach aims to reveal the conflict between communities of Bedowo, Jetak Village, Subdistrict Sidoharjo, The Regency of Sragen with Santri Luwung community accompanied by the involvement of the Islamic paramilitary troops in the conflict chronology of Santri Luwung. The Data was collected through interview, observation, and documentation. This research get the fact that the presence of Islamic paramilitary troops from Solo Residency in the area of conflict turned out to be one of the factors that contributed worsen the problem. They can not be harmony adhesive agent, but on the contrary, that the presence of Islamic paramilitary troops in conflict areas will add a warm existing problems because they have